EVALUATION OF AVAILABILITY AND LEVEL OF WATER REQUIREMENT IN THE SUB OF CIKERUH FLASH - Zarkasih, Muhammad Restu (Indonesia University of Education, 2018)
Water is a vital natural resource for human beings, while the existing water supply can not keep pace with developments that occur in all sectors of life. Therefore research on the evaluation and water compliance level should be done. The method used in this research was descriptive explorative method with population area on all land use in sub-watershed Cikeruh River, sampling research used purposive sampling. Data collection techniques used were field observation, literature study and documentation study. The data analysis was determined by the water balance formula and by counting the amount of water demand for land use in the Cikeruh sub watershed. The results showed that the availability of raw water insub-watershed Cikeruh River was positive in November – April, and May – October is negative, water is sufficient to meet the needs of the household, livestock and industry sectors, so it can not meet the water needs in the agricultural sector.